Growing up, feeling good : A child's introduction to sexuality - Waxman, Stephanie 1944- (Los Angeles : Panjandrum Books, 1979)
Text and numerous photographs examine a person's ever-changing sexual feelings.
Keywords: Sex education, Guide for children -- United States